Pelatihan Pembuatan Media Promosi Kesehatan Berbasis Digital - Muhlizardy Muhlizardy; Nisa Nur Rahma; Retno Tri Utami (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The hospital has a health promotion function for the community. During the pandemic, the health sector underwent many changes, one of which was the use of media. Health promotion is carried out through the activities of providing information, influencing, and helping the community improve their health status. At this time, digital media was more dominantly used in health promotion activities. Canva is an application for producing digital content that is commonly used today. Training on making health promotion media with the Canva application is the goal of implementing this activity, so that later partner health workers can have the knowledge and skills to produce health promotion content digitally. This activity is a community service program carried out at PKU Muhammadiyah Kartusara Hospital in July 2023. Based on the results of this training activity, it can be concluded that the use of digital content in health promotion activities has not been implemented. It is necessary to strengthen the capacity of health workers, especially in training for creating digital content for health promotion.